Enterotoxin Gene Distribution and Genotypes of Bacillus cereus sensu lato Isolated from Cassava Starch (2021)
ABSTRACT : Bacillus cereus is a human pathogenic bacterium found in foods with the potential to cause emesis and diarrhea. This study estimated the presence, toxigenic and genomic diversity of B. cereus s.l. obtained from cassava starch samples collected in bakeries and powdered food companies in Medellín (Colombia). Bacillus cereus s.l. was found in 43 of 75 (57%) cassava starch samples and 98 isolates were obtained. The nheABC, hblCDAB, cytK2, entFM and cesB toxin genes were detected by multiplex PCR and the most frequent operon was nheABC, whereas cesB gene was not found. Twelve toxigenic profiles were determined by the detection of toxin genes, and the most frequent profiles harbored all enterotoxin genes. A broad genomic diversity was detected according to GTG5 -PCR fingerprinting results with 76 B. cereus s.l. grouped in sixteen clusters and the 22 isolates clustering separately. No relationship was observed between genomic background and toxigenic profiles. In general, the results showed a high genomic and enterotoxigenic diversity in B. cereus s.l. found in cassava starch. These results should incentive future studies to understand the distribution of B. cereus s.l. isolated on raw materials in comparison with finished products.